Understanding operating systems - Flynn, Ida M.; McHoes, Ann McIver (Cengage Learning, 2014)
This edition continues to provide a clear and straightforward explanation of operating systems theory and practice. The book's highly regarded structure begins with a discussion of fundamentals before moving on to specific operating systems.